Increasing frequency and changing nature of Saharan dust storm events in the Carpathian Basin (2019–2023) – the new normal? - Varga, György; Rostási, Ágnes; Meiramova, Aida; Dagsson-Waldhauserová, Pavla; Gresina, Fruzsina (Hungarian Geographical Bulletin, 2024)
The number and intensity of Saharan dust storm events identified in Europe has been increasing over the last decade. This can be explained by the role of ongoing climate change. An extension of previous studies covering a 40-year period is presented in this paper, with new data on the frequency, synoptic meteorological background, source areas, grain size, grain shape and general mineralogy of deposited dust for the period 2019–2023 in the Carpathian Basin. A total of 55 dust storm episodes have been identified in the region over the five-year period, which is significantly higher than the long-term average. The classification based on synoptic meteorological background clearly showed that the frequency of circulation types with a more pronounced meridional component increased and dust material reached further north more frequently than before. In several cases, large amounts of dust were deposited, from which samples were collected and subjected to detailed granulometric analysis. The varied grain size data showed that coarse silt (20–62.5 μm) and sand (62.5 < μm) fractions were also present in large quantities in the transported dust material.